Fragmentation of the gastrodermis and detachment of zooxanthellae in symbiotic cnidarians: a role for hydrogen peroxide and Ca2+ in coral bleaching and algal density control - Sandeman, I. M. (2006)
Coral bleaching involves the detachment of zooxanthellae and the simultaneous fragmentation of the gastrodermis. Results obtained with a cell permeant fluorescent probe for calcium ions (Ca2+) indicates that “thermal” bleaching is the result of a temperature related breakdown of the Ca2+ exclusion system. “Solar” bleaching, which takes place at lower temperatures and is driven by light, is the result of a build-up of photosynthetically produced hydrogen peroxide in the tissues. Gastrodermal tissue with its symbionts, scraped from between septa of corals, was observed under controlled conditions of high light and temperature. Pieces of gastrodermis round off, zooxanthellae move to the surface, protrude from the surface and after a delay, detach, surrounded by a thin layer of host cytoplasm, inclusions and plasma membrane. The higher the temperature and light level the shorter the delay and higher the rate of algal detachment. Fragmentation by the ballooning-out and detachment of small spheres of cytoplasm (bleb formation) takes place simultaneously. This is likely to be due to oxidation, by hydrogen peroxide (H2O2), of -SH groups on the cytoskeleton and its attachment to the plasma membrane. Ground, polished and stained thin acrylic resin sections reveal similar processes taking place in artificially bleached corals. Isolated zooxanthellae and whole corals are shown to release H2O2 in the light. This process of algal detachment and fragmentation that takes place at normal sea temperatures may underlie the mechanism limiting algal populations in the gastrodermis and may be localized to areas with a concentration of algae near the membrane. At above-normal temperatures under the synergistic effect of light and temperature, the rate of production of H2O2 exceeds the rate at which can it be lost by diffusion or destroyed and H2O2 accumulates. This results in damage to the calcium exclusion system, detachment of zooxanthellae into the coelenteron and fragmentation of the gastrodermis. Rev. Biol. Trop. 54 (Suppl. 3): 79-96. Epub 2007 Jan. 15.